LEVERAGE, LIKUIDITAS, DAN PROFITABILITAS DALAM KINERJA KEUANGAN - Edy Zulfiar (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to synthesize prior research on leverage, liquidity, and profitability in explaining financial performance, firm value, and financial risk. The study uses a Systematic Literature Review approach based on an extraction file containing 40 articles. Articles were selected by publication year, topic relevance, research focus, metadata completeness, and DOI availability. After screening, 31 articles published between 2009 and 2021 were analyzed using thematic analysis. The findings show that leverage is the most dominant theme because it relates to capital structure, firm value, investment flexibility, and bankruptcy risk. Liquidity explains short-term financial stability, yet its effect varies across sectors and research models. Profitability, especially ROA, ROE, EPS, and profit margin, appears as the most consistent indicator for assessing financial performance and market response. The review also finds that corporate governance, CSR, reporting quality, and external economic conditions strengthen the explanation of financial performance. Future studies need an integrated model that combines financial ratios, governance, sustainability, and macroeconomic variables.